Muḍāraba Fund of Bank Jateng Syariah Cabang Surakarta (BJSCS) According to Dewan Syariah National-Majelis Ulama Indonesia (DSN-MUI) - Dyah Ayu (Muhammadiyah University Press, 2019)
This study aims to illustrate the concept of muḍāraba fund applied by BJSCS. The type of this research is descriptive and qualitative. This study describes the procedures and implementation of muḍāraba fund as well as its compliance with the Fatwa of DSN-MUI. The employed data in this study was obtained through interviews with the finansial officer as representatives of BJSCS who act as key informants. The results reveal that the concept of muḍāraba fund in BJSCS has not been fully in compliance with the Fatwa of DSN-MUI. It is based on firtsly, Fatwa of DSN-MUI number (6) stating that “The Sharia Finansial Institution as the provider of funds shall bear all losses resulting from muḍāraba unless the muḍarib (entrepreneur) makes a deliberate, negligent or counterproductive mistake.